2016
DOI: 10.1021/acs.analchem.6b00204
|View full text |Cite
|
Sign up to set email alerts
|

Combined Electron Paramagnetic Resonance and Atomic Absorption Spectroscopy/Inductively Coupled Plasma Analysis As Diagnostics for Soluble Manganese Species from Mn-Based Positive Electrode Materials in Li-ion Cells

Abstract: Manganese dissolution from positive electrodes significantly reduces the durability of lithium-ion batteries. Knowledge of dissolution rates and oxidation states of manganese ions is essential for designing effective mitigation measures for this problem. We show that electron paramagnetic resonance (EPR) combined with atomic absorption spectroscopy (AAS) or inductively coupled plasma (ICP) can determine both manganese dissolution rates and relative Mn(3+) amounts, by comparing the correlation between EPR and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 18 publications
3
54
4
Order By: Relevance
“…Furthermore, the dissolution of Mn 2+ was accelerated at elevated temperatures due to the decomposition of the electrolyte. The absence of Mn 3+ is contrary to those studies, which reported dissolution of Mn 2+ and Mn 3+ from LMO or LNMO cathode materials into LIB electrolytes [38, 39].…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, the dissolution of Mn 2+ was accelerated at elevated temperatures due to the decomposition of the electrolyte. The absence of Mn 3+ is contrary to those studies, which reported dissolution of Mn 2+ and Mn 3+ from LMO or LNMO cathode materials into LIB electrolytes [38, 39].…”
Section: Discussioncontrasting
confidence: 84%
“…Nevertheless, several studies report on dissolved Mn 3+ being the main manganese species in common electrolyte in case of the LMO cathode, with abundances of 67–78% after storage and 60–80% after electrochemically treatment in LMO||Graphite cells. For LNMO, the Mn 3+ amount in the electrolyte after storage was reported to be 12–44% of total dissolved manganese [38, 39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inductive loops have been ascribed to electrochemical asymmetries, which are observed within the studied range of potentials. Some hypotheses have been proposed in the literature to explain this phenomenon, including the heterogeneity of the ions distribution inside the electrode to generate concentration cells between different particles of electrode or the phase change of the active material during the EIS measurement[34]. The charge transfer resistance is further decreased by reducing the potential to -1.4 V.…”
mentioning
confidence: 99%
“…However, Shilina et al recently argued that Mn 3+ not Mn 2+ is the dominant species dissolved from the LiMn 2 O 4 material while Mn 2+ is predominant for the LiNi 0.5 Mn 1.5 O 4 material. 19 This result is contradicting to the previous knowledge that Mn 2+ ions are the only soluble species that dissolve from the LiMn 2 O 4 cathode material. While this aspect needs to be investigated further, it was quite clear that additional manganese was observed with decomposed electrolyte products in the SEI layers of the graphite surface under various experimental conditions.…”
mentioning
confidence: 70%